Histories of Byzantium: some remarks on the early manuscripts of Theophanes’ Chronicle - Montinaro, Federico (Semitica et Classica, 2015)
Abstract In the first part of this article, the author summarizes recent scholarship on the earliest manuscripts of the Chronographia attributed to Theophanes the Confessor (d. 817 or 818). In the second part, he draws attention to overlooked evidence for the early circulation of the chronicle found in the preface to the Latin translation by Anastasius the Librarian, composed ca. 870. Abstract Dans la première partie de cette contribution, l’auteur résume les nouveaux acquis relatifs aux plus anciens manuscrits de la Chronographie attribuée à Théophane le Confesseur († 817 ou 818). Dans la seconde, il repère des renseignements méconnus sur la première circulation de cette même œuvre dans la préface à la traduction latine par Anastase le Bibliothécaire, composée autour de 870.